EcoRevolusi Sungai: Education, Innovation, and Circular Economy Approaches to Address Flooding and Waste Issues in Wawonduru Village - Julkifli, Julkifli; Ardiansyah, Ardiansyah; Aidin, Aidin (Abdi Masyarakat, 2025)
Flooding and river pollution in Wawonduru Village, Woja District, Dompu Regency are primarily caused by low public awareness of waste management and the absence of an integrated waste sorting and management system. This condition motivated the implementation of a community service program entitled EcoRevolusi Sungai, which aims to enhance community capacity and participation in waste management based on circular economy principles and technological innovation. The program employed a participatory approach encompassing socialization activities, training, workshops, the provision of waste-sorting facilities, mentoring, and evaluation. The target groups included Karang Taruna ASWAD, the Wawonduru Student and Youth Association (KEMAP-W), and the surrounding community. The results indicate the availability of waste-sorting facilities in the form of Five-Category Waste Bins (T-5K), the implementation of the SIMAS SAKIKU Digital Waste Bank System, the utilization of organic waste composters, and an improvement in the knowledge and skills of partners in community-based waste management. Socialization and mentoring activities encouraged behavioral changes from indiscriminate waste disposal toward more responsible waste sorting and management practices. Furthermore, the role of youth organizations as managers of the waste bank and digital system was strengthened, leading to the establishment of a sustainable community-based waste management system that contributes to reducing environmental pollution and flood risks in Wawonduru Village. The EcoRevolusi Sungai program demonstrates potential as a community engagement model for village-level environmental management and flood risk reduction.